Sufficient conditions of starlikeness and convexity for functions of complex order - Saibah Siregar; Mohd Nazran Mohammed Pauzi; Maslina Darus (Penerbit Universiti Kebangsaan Malaysia, 2020)
Let A be the class of normalised and analytic functions defined in the unit disc {:||1}.Uzz In this paper we study the expression 2()1,,()()zfzzzUbfzbfz for some (0) and (\{0}bb as a criteria for starlikeness and convexity at analytic functions of complex order.